Odpowiedzi

2010-03-29T15:43:42+02:00
2x-8+6x+9=4x+8-5+5x
2x+6x-4x-5x=8-5+8-9
-x=2
x=-2

x+1/5=1-2x-3/6
x+2x=1-3/6-1/5
3x=2.5/:3
x=5/6
1 5 1
2010-03-29T15:43:56+02:00
2(x-4)+3(2x+3)=4(x+2)-5(1-x)
2x-8+6x+9=4x+8-5+5x
8x+1=9x+3 |-8x
1=x+3 |-3
-2=x

x+1/5=1 - 2x-3/6 |x30
x+6=1-2x-15
x+6=-14-2x |+2x
3x+6=-14 |-6
3x=-20 |:3
x=-20/3
1 5 1
2010-03-29T15:44:31+02:00
2(x-4)+3(2x+3)=4(x+2)-5(1-x)
2x-8+6+9 =4x +8 -5 +5x
2x-4x-5x = 8-5+8-6-9
-7x = -4 /:(-7)
x= 4/7

x+1/5=1 - 2x-3/6
x+2x = 1 -3/6-1/5
3x = 9/30 /:3
x= 0,1
1 5 1